Enriching the Mediterranean diet could nourish the brain more effectively - Picone, Pasquale; Girgenti, Antonella; Buttacavoli, Miriam; Nuzzo, Domenico (Frontiers in Nutrition, 2024)
The increasing prevalence of neurodegenerative disorders represents a challenge to the global health of all nations and populations, particularly with increasing longevity. Urgent prevention strategies are therefore needed, and one opportunity may be to explore the relationship between dietary patterns and brain health which has emerged as a promising strategy. Numerous studies indicate that dietary choices have a significant impact on cognitive function, memory and the risks of neurological disorders, recognizing the dynamic role of diet in maintaining cognitive abilities. One of the most studied dietary styles, tThe Mediterranean diet, characterized by healthy, plant-based foods fats and moderate consumption of animal products, has demonstrated its neuroprotective potential. Rich in antioxidants, vitamins and polyphenols, this diet shows consistent associations with cardiovascular health and cognitive function. Some less talked about foods, such as seaweed, blackcurrants, Lion's Mane mushroom and chia seeds, are emerging as potential brain health boosters. These and other new foods could enrich the Western diet making it capable of effectively preventing neurological disorders. Despite promising scientific data, difficulties persist in understanding the complex relationship between nutrition and brain health. Individual variability, long-term dietary adherence, comorbidities, and the need for rigorous clinical evidence pose obstacles. In this review, we would like to focus our attention on the future of brain-diets, which should involve accessible, personalized and evidence-based interventions, providing hope against the challenges posed by neurodegenerative diseases. In fact, as research progresses, more and more attention are being placed on to brain health, promising a harmonious and resilient cognitive landscape for individuals and society.